2018
DOI: 10.3389/fnagi.2018.00291
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A Suppresses Beta Amyloid in APP Expressing Cells: Studies for Tat and Cocaine Associated Neurological Dysfunctions

Abstract: Neurological disorders are the biggest concern globally. Out of ~36 million human immunodeficiency virus (HIV) positive people, about 30%–60% exhibit neurological disorders, including dementia and Alzheimer’s disease (AD) like pathology. In AD or AD like neurological disorders, the pathogenesis is mainly due to the abnormal accumulation of extracellular amyloid beta (Aβ). In this era of antiretroviral therapy, the life span of the HIV-infected individuals has increased leading towards increased neurocognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…We observed these cells at 10× resolution. This study aligns with our prior results that WA has the ability to reduce Aβ in vitro (Tiwari et al, 2018).…”
Section: Congo Red Stain-based Quantification Of Amyloid-beta In Withsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed these cells at 10× resolution. This study aligns with our prior results that WA has the ability to reduce Aβ in vitro (Tiwari et al, 2018).…”
Section: Congo Red Stain-based Quantification Of Amyloid-beta In Withsupporting
confidence: 93%
“…In the brain of AD patients, NF-κB activation is predominantly found in neurons and glial cells present in the vicinity of Aβ plaque deposition (Terai et al, 1996;Boissière et al, 1997;Kaltschmidt et al, 1997;Lukiw and Bazan, 1998). In our earlier study, we have observed that withaferin A (WA), a steroidal lactone, derived from the plant Withania somnifera inhibits Aβ levels in amyloid overexpressing SH-SY5Y cells (SH-APP) (Tiwari et al, 2018). Based on these observations and reports on the role of WA in inhibiting the NF-κB-mediated neuroinflammation (Heyninck et al, 2014;Martorana et al, 2015), in this study we have utilized WA to study the Aβ levels and associated NF-κB-mediated neuroinflammation in SH-APP and microglial mixed cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported increased NFκB activation in AD and pointed to a relationship with Aβ pathology ( 108–111 ). Moreover, Withaferin A has been identified as an inhibitor of NFκB signaling ( 112 , 113 ) and has shown therapeutic potential to protect against Aβ toxicity ( 114 ), and we found Withaferin A is a modulator of CM9, CM4 and CM1 ( Supplementary Material, Fig. S11 ).…”
Section: Resultsmentioning
confidence: 80%
“…There are promising drugs against Aβ toxicity,75 but in order to explore their maximum effect on CNS cells, there is a need of nanocarriers to be employed. Availability of drugs in the CNS is the major issue faced in the field of therapeutics against AD.…”
Section: Need For Nanotechnology As a Therapeutic Strategy Across Thementioning
confidence: 99%